Ultrastructural and immunohistochemical characteristics of the anterior abdominal wall tissue in experimental plastics of ventral hernias. - Malkov, I. I. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. The active retrieval of methods for the increase of the efficiency of ventral hernia alloplasty is performed now; however the structural-functional changes of scar and muscle tissues during their reorganization are still little studied. Objective. The purpose of the work was to determine cellular and ultrastructural changes in the anterior abdominal wall with experimental alloplasty of ventral defects. Methods. The morphological analysis was carried out during 1 year. Transmission electron microscopy and immunohistochemistry of vascular markers CD34 and VEGF were used. Results. Early tissue reactions after plastics of a large ventral defect include expressive manifestations of acute aseptic inflammation and degenerative changes in muscle-aponeurotic structures in conditions of significant biomechanical tissue tension in the healing zone of the wound, regardless of the presence or absence of prosthesis material. The use of polypropylene mesh without tension and alignment of the edges of the defect reduces the severity of early ultrastructural damage. Immunohistochemical characteristic of muscle tissue on markers VEGF and SD34 within 1 year after hernioplasty of large ventral defect under conditions of tension of tissues testifies to the preservation of pathological changes and violation of the microvascular component. Prevention of biomechanical stresses of the muscular-aponeurotic layer leads to normalization of the distribution and expression levels of VEGF and CD34. Conclusion. In conditions of significant tissue tension after the plastics of a large ventral defect, there is a preservation of destructive ultrastructural changes in the microvessels and muscle-aponeurotic structures, regardless of the presence or absence of a monofilament polypropylene mesh. The lack of significant tissue tension creates conditions for the full integration of the prosthesis to muscle-aponeurotic structures.